Disability‐Adjusted Life Years (DALYs) due to Breast, Cervical, Colorectal and Oral Cancers in Taiwan Regions - Cheng‐Chieh Hsieh; Si‐Yu Chen; Chun‐Hui Lin; Szu‐Chieh Chen; Chung‐Min Liao (Cancer Medicine)
ABSTRACT Background Cancer is a leading cause of death globally, with significant variations in incidence and mortality rates among different cancer types and regions. In Taiwan, breast cancer (BC), cervical cancer (CxCa), colorectal cancer (CRC), and oral cancer (OC) are prevalent and have prompted government‐led screening programs to mitigate their impact. This study aims to assess the burden of these cancers at the county scale using disability‐adjusted life years (DALYs) as a metric, focusing on the years 2010, 2015, 2018, 2019, and 2020. Methods Data on cancer incidence, mortality, disability weights, and treatment outcomes were sourced from the Taiwan HPA, Ministry of Health and Welfare, and Taiwan Cancer Registry. Years of life lost (YLLs) and years lived with disability (YLDs) were calculated for each cancer, considering age, stage, and treatment. The correlation between cancer screening rates and disease burden also conducted. Results The analysis highlights significant trends in cancer mortality, incidence, and disease burden in Taiwan from 2010 to 2020. BC and CRC showed rising ASMR and DALYs rates, while CxCa experienced consistent declines. OC had a fluctuating pattern, particularly in eastern regions. YLLs contributed significantly to DALYs for all cancers, emphasizing premature mortality's role in the disease burden. Screening rates, particularly for BC and CxCa, correlated with changes in burden, with BC rates increasing and CxCa decreasing, reflecting the impact of preventive measures on cancer outcomes. Conclusions The findings underscore the importance of targeted interventions and evidence‐informed resource allocation to address regional differences in cancer burden in Taiwan.